Rapid Data Exchange Using RFID for Examination Result Process - Omar, Nurul Syuhada (Universiti Teknologi PETRONAS, 2016)
The project was involved the application of the Radio Frequency Identification Device. The purpose of this research is to help people who working with the key in data process so that their work could be faster and accurate. This project wills only focusing of the examination result process of key in marks in the Universiti Teknologi PETRONAS. Lecturer usually will waste lots of time during key in marks of student paper after the examination. They have to make sure every data type is accurate and they have to complete within the stipulated time.